Tumor Lysis Syndrome - Jessica Brooks; Nadia Huancahuari; Kathleen Wittels (Association of American Medical Colleges, 2014)
Abstract This simulation case is designed to educate medical students and residents about tumor lysis syndrome. Participants are responsible for caring for a simulated patient with tumor lysis syndrome, whereby they evaluate, diagnose, and treat the critically ill patient. This case has been run for emergency medicine residents during their simulation curriculum. Resident experience with this case was overwhelmingly positive. In a postcase survey, 89% of participants felt that their ability to diagnose and treat tumor lysis syndrome was enhanced by the case. Similarly, 78% of residents responded that their knowledge of how to treat hyperkalemia related to tumor lysis syndrome was enhanced by this case, and 89% felt their ability to treat hyperuricemia related to tumor lysis syndrome was enhanced.